STUDI ANALISIS TENTANG LINEARITAS KOMPONEN RENCANA PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK DI PERSEKOLAHAN KOLESE XAVERIUS AMBON - Rahayaan, Korneles; Reresi, Marsianus (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2020)
This research aims to examine the linearity of the Learning Plan component of the Catholic Religious Education. This research is the most relevant study in relation to the pedagogical and professional competence of teachers in organizing learning at the Xaverius College School of Ambon. The focus of this qualitative research is to determine the linearity of the learning component of Catholic Religious Education in Xaverius College School of Ambon. The data collection technique used in this research is to use documentation study which is then analyzed in terms of completeness and systematic, clarity of the content of the learning components and the linearity of the learning components.